Effects of Reduced-Dose Anti-Human T-Lymphocyte Globulin on Overall and Donor-Specific T-Cell Repertoire Reconstitution in Sensitized Kidney Transplant Recipients - Aschauer, Constantin; Jelencsics, Kira; Hu, Karin; Gregorich, Mariella; Reindl-Schwaighofer, Roman; Wenda, Sabine; Wekerle, Thomas; Heinzel, Andreas; Oberbauer, Rainer (Frontiers in Immunology, 2022)
Background Pre-sensitized kidney transplant recipients have a higher risk for rejection following kidney transplantation and therefore receive lymphodepletional induction therapy with anti-human T-lymphocyte globulin (ATLG) whereas non-sensitized patients are induced in many centers with Basiliximab. The time course of lymphocyte reconstitution with regards to the overall and donor-reactive T-cell receptor (TCR) specificity remains elusive. Methods/Design Five kidney transplant recipients receiving a 1.5mg/kg ATLG induction therapy over seven days and five patients with 2x20mg Basiliximab induction therapy were longitudinally monitored. Peripheral mononuclear cells were sampled pre-transplant and within one, three and 12 months after transplantation and their overall and donor-reactive TCRs were determined by next generation sequencing of the TCR beta CDR3 region. Overall TCR repertoire diversity, turnover as well as donor specificity were assessed at all timepoints. Results We observed an increase of the donor-reactive TCR repertoire after transplantation in patients, independent of lymphocyte counts or induction therapy. Donor-reactive CD4 T-cell frequency in the ATLG group increased from 1.14%+-0.63 to 2.03%+-1.09 and from 0.93%+-0.63 to 1.82%+-1.17 in the Basiliximab group in the first month. Diversity measurements of the entire T-cell repertoire and repertoire turnover showed no statistical difference between the two induction therapies. Difference in mean clonality between groups was 0.03 and 0.07 pre-transplant in the CD4 and CD8 fraction respectively and was not different over time (CD4: F(1.45, 11.6)=0.64 p=0.496; CD8: F(3, 24)=0.60 p=0.620). Mean difference in R20, a metric for immune dominance, between groups was -0.006 in CD4 and 0.001 in CD8 T-cells and not statistically different between the groups and subsequent timepoints (CD4: F(3, 24)=0.85 p=0.479; CD8: F(1.19, 9.52)=0.79 p= 0.418). Conclusion Reduced dose ATLG induction therapy led to an initial lymphodepletion followed by an increase in the percentage of donor-reactive T-cells after transplantation similar to Basiliximab induction therapy. Furthermore, reduced dose ATLG did not change the overall TCR repertoire in terms of a narrowed or skewed TCR repertoire after immune reconstitution, comparable to non-depletional induction therapy.